A highly stable solid-state supercapacitor device based on robust layer-by-layer electrodeposited poly-(3, 4-ethylenedioxythiophene)-reduced graphene oxide–molybdenum disulfide nanocomposite electrode. (1st December 2022) - Singh, Bhupender; Kaur, Ranjeet; Kaur, Randeep; Singh, Kulvinder; Rana, Shweta
Abstract: A ternary nanocomposite film of PEDOT-rGO-MoS2 for a symmetrical solid-state supercapacitor device has been fabricated via in-situ interconversions by employing efficient electrochemical approach. The higher porosity offered by popcorn like microstructures of PEDOT has enabled better stacking within PEDOT-rGO-MoS2 composite resulting in superior supercapacitive performance. The obtained electrode exhibits good volumetric capacitance (887.6 F cm −3 ) and high volumetric energy density (123 mWh cm −3 ) with high-power density (2930 mW cm −3 ). The efficiency in the supercapacitor performance originates from the synergy of the trio forming a well-integrated optimized energy storage system. Assembly of composite films into a solid-state symmetrical device with PVA-KCl gel-electrolyte has resulted in excellent cyclic stability, good capacitive retention of 98.3 % and coulombic efficiency of 100.2 % over 10, 000 cycles. The obtained symmetrical device offered high areal energy density (1.1 μWh cm −2 ) has been successfully evaluated for its practical utility in the configuration of four devices connected in series with an output of 25 min to illuminate green LED. The findings pave a promising way for the development of energy efficient microelectronics by using the present device structure in future energy storage applications. Graphical abstract: Unlabelled Image Highlights: Fabrication of layer-by-layer electrodeposited ternary composite for supercapacitor electrode material. Elaborative optimization of designed material to achieve excellent synergy between electrode components. Significantly high cycling stability over large number of charge discharge cycles with remarkably high capacitive retention. Highly robust and portable solid state device for practical applications.